Feasibility of Flat Panel Angiographic CT after Intravenous Contrast Agent Application in the Postoperative Evaluation of Patients with Clipped Aneurysms - Psychogios, M.-N.; Wachter, D.; Mohr, A.; Schramm, P.; Frölich, A.-M.; Jung, K.; Rohde, V.; Knauth, M. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Important findings, such as aneurysm remnants or major arterial occlusion, can be detected on intra- or postoperative angiography after surgical clipping of intracranial aneurysms. The purpose of this study was to evaluate the feasibility of IV-ACT for the postoperative detection of residual aneurysms and parent vessel patency compared with IA-DSA, which was selected as the standard reference method. MATERIALS AND METHODS: Twenty-two patients with 27 aneurysms treated by surgical clipping were examined by using both IA-DSA and IV-ACT. Both diagnostic procedures were performed on an FPD-equipped angiography system. Postprocessing of IV-ACT acquisitions was performed on a dedicated workstation producing multiplanar reformations and maximum intensity projections of the clip region and other intracranial arteries. Three interventional neuroradiologists independently evaluated both procedures. RESULTS: A residual aneurysm was delineated in 10 cases with IA-DSA. Sufficient opacification of the intracranial vessels was assigned in 26 IV-ACT cases. Due to metal artifacts, IV-ACT images were tagged as “not diagnostic” on 8 occasions. In the other 19 aneurysms, a residual aneurysm was delineated in 6 cases—all 6 being true-positive compared with IA-DSA—and was excluded in the remaining 13 cases—all true-negative. Even small aneurysm remnants with a diameter of 1.5 mm were detected with IV-ACT. CONCLUSIONS: Currently IV-ACT cannot be recommended as a routine tool for postoperative evaluation of clipped aneurysms due to metal artifacts in 30% of the examinations. These artifacts appear with multiple normal-sized or large clips. In patients with single or multiple small clips, IV-ACT can reliably show aneurysm remnants. ACTflat-panel angiographic CTCIconfidence intervalCTACT angiographyCTDIwweighted CT dose indexDSAdigital subtraction angiographyFPDflat panel detectorIAintra-arterialIV-ACTflat panel CTA after intravenous contrast agent applicationMDCTAmultidetector row CT angiographyMRAMR angiography